1994
DOI: 10.1007/bf00180008
|View full text |Cite
|
Sign up to set email alerts
|

H3 receptor-mediated inhibition of noradrenaline release: an investigation into the involvement of Ca2+ and K+ ions, G protein and adenylate cyclase

Abstract: The present study was aimed at the identification of mechanisms following the activation of histamine H3 receptors. Mouse brain cortex slices preincubated with 3H-noradrenaline were superfused and the (H3 receptor-mediated) effect of histamine on the electrically evoked tritium overflow was studied under a variety of conditions. The extent of inhibition produced by histamine was inversely related to the frequency of stimulation used to evoke tritium overflow and to the Ca2+ concentration in the superfusion med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 26 publications
4
34
1
Order By: Relevance
“…a larger depression was observed at lower external calcium concentrations. A similar relationship has previously been demonstrated for H× receptor-mediated depression of histamine (Arrang et al 1985) and noradrenaline release (Schlicker et al 1994). Such a relationship is consistent with an effect of histamine on calcium influx (i.e.…”
Section: Effects On Calcium Influxïcalcium Channelssupporting
confidence: 87%
See 1 more Smart Citation
“…a larger depression was observed at lower external calcium concentrations. A similar relationship has previously been demonstrated for H× receptor-mediated depression of histamine (Arrang et al 1985) and noradrenaline release (Schlicker et al 1994). Such a relationship is consistent with an effect of histamine on calcium influx (i.e.…”
Section: Effects On Calcium Influxïcalcium Channelssupporting
confidence: 87%
“…Thus, we conclude that it is more likely that histamine inhibits several types of presynaptic calcium channels rather than activating presynaptic potassium channels. Studies on the histamine H×-mediated inhibition of cortical noradrenaline release also concluded that potassium channels were not responsible for the effect (Schlicker et al 1994). Blockers or activators of ATP-sensitive potassium channels did not affect the histaminergic inhibition.…”
Section: Blockade Of Potassium Channelsmentioning
confidence: 99%
“…This autoinhibition by H 3 receptor agonists [e.g., (R)-a-methylhistamine; 33] and its removal by H 3 receptor antagonists/partial agonists can be demonstrated in recordings from TMN neurons. As presynaptic heteroreceptors, H 3 receptors control the release of several other transmitters, including biogenic amines (Schlicker et al, 1994(Schlicker et al, , 1999, acetylcholine (Blandina et al, 1996;Arrang, 2007), GABA (Jang et al, 2001), and glutamate; field potentials evoked by stimulation of glutamate fiber bundles, e.g., in hippocampus or striatum, show a marked decrease in the presence of an H 3 receptor agonist (Brown and Haas, 1999;Doreulee et al, 2001) (Fig. 12).…”
Section: Functionmentioning
confidence: 99%
“…Besides being histaminergic auto-receptors, H 3 receptors also function as presynaptic heteroreceptors controlling the release of serotonin (31), acetylcholine (32) and several other neurotransmitters (33,34). It has been shown that histaminergic H 3 antagonists (ciproxifan, clobenpropit and thioperamide), directly administered to the basolateral amygdala, decreased spontaneous acetylcholine release.…”
Section: Discussionmentioning
confidence: 99%